Endosomal pH in neuronal signaling and synaptic transmission: role of Na+/H+ exchanger NHE5 - Diering, Graham H.; Numata, Masayuki (Frontiers in Physiology, 2014)
Neuronal precursor cells extend multiple neurites during development, one of which extends to form an axon whereas others develop into dendrites. Chemical stimulation of N-methyl D-aspartate (NMDA) receptor in fully-differentiated neurons induces projection of dendritic spines, small spikes protruding from dendrites, thereby establishing another layer of polarity within the dendrite. Neuron-enriched Na+/H+ exchanger NHE5 contributes to both neurite growth and dendritic spine formation. In resting neurons and neuro-endocrine cells, neuron-enriched NHE5 is predominantly associated with recycling endosomes where it colocalizes with nerve growth factor (NGF) receptor TrkA. NHE5 potently acidifies the lumen of TrkA-positive recycling endosomes and regulates cell-surface targeting of TrkA, whereas chemical stimulation of NMDA receptors rapidly recruits NHE5 to dendritic spines, alkalinizes dendrites and down-regulates the dendritic spine formation. Possible roles of NHE5 in neuronal signaling via proton movement in subcellular compartments are discussed.